Deliverable 5.11 Integration of new processing services V2 - Caumont, Hervé; Vaccari, Simone; Storheim, Espen; Hamre, Torill (Zenodo, 2022)
Within INTAROS, WP5 (Data integration and management) is tasked with designing and implementing evolution of the cloud platform and tools for the iAOS (integrated Arctic Observation System). This document in its volume V2 defines additional resources for iAOS data exploitation and processing, in particular in the context of the WP5 support to the WP6 iAOS Showcase applications. These new resources are delivered as a collection of R and Python-based Jupyter Notebooks, a state of the art approach for collaborative science, interactive data analysis and management of software code experiments. This V2 report embeds the results previously delivered as part of the V1 release, these can be found in the sections 3. “C-PAD Service Specification” (Characterization of Passive Acoustic Data) and 4. “TS-SIC Service Specification” (Time Series of Sea Ice Concentration). For these two services, the update between D5.7 (V1) and D5.11 (V2) was done only on the structure of the chapters "Software modules required", "Cloud resources allocation" and "Roadmap for future development”. No new developments were performed here. The new results are focused on the exploitation of interoperability protocols (OPeNDAP) as promoted by INTAROS for the iAOS, and on the use of the RGeostats Geostatistical software library. They are presented in section 5. “TS-CTD Service Specification” (Time Series of Conductivity-Temperature-Depth) and in section 6. “iAOS Showcase Service Specification”.